Evaluation of phase-feeding strategies and compensatory growth in grow-finish pigs and supplementation of probiotics to sows and progeny - Boscato Menegat, Mariana (Kansas State University, 2019)
The dissertation consists of 5 chapters comprising a review of literature on compensatory growth following lysine restriction in grow-finish pigs, evaluation of phase-feeding strategies for grow-finish pigs, supplementation of Bacillus subtilis-based probiotic to sows, nursing and nursery pigs, and addition of pharmacological levels of copper to nursery diets. Chapter 1 presents a review of the current state of knowledge on compensatory growth induced by lysine restriction in grow-finish pigs. The review discusses the basis, types, factors, and dynamics involved in compensatory growth; develops a database from peer-reviewed literature to standardize comparisons to characterize the occurrence of compensatory growth; and provides practical considerations for compensatory growth under commercial conditions. Chapter 2 describes four experiments conducted to evaluate phase-feeding strategies based on lysine specifications and number of dietary phases for 27-to 127-kg grow-finish pigs. Phase-feeding strategies provide performance advantages over feeding a single dietary phase throughout the grow-finish period. Simplification of feeding strategies from 4 to 3 or 2 dietary phases with Lys specifications at 98% to 100% of estimated requirements for growth rate does not compromise overall growth performance and carcass characteristics of grow-finish pigs from 27 to 127 kg BW. Although, using feeding programs with fewer dietary phases and Lys set slightly below the requirements can compromise growth performance if initial BW and feed intake in the grow-finish period are lower than expected. Feeding strategies with Lys specifications set at 96% of estimated requirements compromise performance of grow-finish pigs unless Lys requirements are fully met in late finishing. In chapter 3, a study evaluates the effects of daily oral dose of Bacillus subtilis C-3102 probiotic to nursing piglets on fecal consistency, fecal microbes, and pre-weaning performance. A daily oral dose of Bacillus subtilis C-3102 did not influence pre-weaning growth performance and fecal consistency of nursing piglets and only influenced Bacillus sp. fecal microbial population. In chapter 4, a study evaluates the effects of providing a Bacillus subtilis C-3102 probiotic to sows during gestation and lactation and to progeny after weaning on performance, fecal consistency, and fecal microbes. Providing a Bacillus subtilis C-3102 probiotic did not elicit noteworthy improvements in performance, fecal consistency, or fecal microbial populations in gestation, lactation, or nursery periods, but there was a benefit on sow lactation feed intake. Fecal microbial analysis indicated a maternal-progeny intestinal microbiota relationship with pigs born from probiotic-fed sows displaying similar fecal microbial population as sows. However, pigs born from probiotic-fed sows demonstrated reduced growth rate and feed consumption in late nursery. In chapter 5, a study evaluates the effect of added copper, alone or in combination with a feed-grade antimicrobial, on growth performance of 7- to 20-kg nursery pigs. The addition of 200 mg/kg copper from copper sulfate or 440 mg/kg chlortetracycline in nursery dies for 28 days exerted growth promotional effects on weaned pigs. The lack of interaction suggests the responses of copper and chlortetracycline on growth performance of nursery pigs are as efficacious when fed alone or in combination.
Keywords: Compensatory growth; Lysine; Phase feeding; Probiotic; Swine